2015
DOI: 10.1002/adfm.201502566
|View full text |Cite
|
Sign up to set email alerts
|

Ambient‐Dried Cellulose Nanofibril Aerogel Membranes with High Tensile Strength and Their Use for Aerosol Collection and Templates for Transparent, Flexible Devices

Abstract: The application potential of cellulose nanofibril (CNF) aerogels has been hindered by the slow and costly freeze-or supercritical drying methods. Here, CNF aerogel membranes with attractive mechanical, optical and gas transport properties are prepared in ambient conditions with a facile and scalable process. Aqueous CNF dispersions are vacuum-filtered and solvent exchanged to 2-propanol and further to octane, followed by ambient drying. The resulting CNF aerogel membranes are characterized by high transparency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
148
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 67 publications
3
148
1
5
Order By: Relevance
“…[10][11][12][13][14][15][16] Therefore, nanopaper has recently received much attention as a substrate for flexible electronics. 9,[17][18][19][20][21][22][23][24][25][26][27][28][29] To date, various electronic devices including organic/inorganic thin-film transistors, 9,21-23 light-emitting diodes, 24 solar cells, 23,25,26 antennas 27,28 and triboelectric generators 29 have been demonstrated on nanopaper substrates. However, a nonvolatile memory, which is the essential component for IoE technology, has not been demonstrated on a nanopaper substrate so far.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Therefore, nanopaper has recently received much attention as a substrate for flexible electronics. 9,[17][18][19][20][21][22][23][24][25][26][27][28][29] To date, various electronic devices including organic/inorganic thin-film transistors, 9,21-23 light-emitting diodes, 24 solar cells, 23,25,26 antennas 27,28 and triboelectric generators 29 have been demonstrated on nanopaper substrates. However, a nonvolatile memory, which is the essential component for IoE technology, has not been demonstrated on a nanopaper substrate so far.…”
Section: Introductionmentioning
confidence: 99%
“…

high tortuosity and complex flow channels, which may cause high flow resistance, specifically due to agglomeration when the reactant gas flows through the Ni catalysts. [34][35][36][37] Mechanically superstrong composites have been demonstrated by incorporating cellulose nanofibers. For example, transparent films based on cellulose nanofibers are promising replacements of plastics for biodegradable electronics.

…”
mentioning
confidence: 99%
“…By contrast, more opaque films have been achieved in cases where cellulose reinforcements were either poorly wetted, agglomerated (Santos et al 2014;Ambrosio-Martin et al 2015b), or simply large relative to the wavelength of light . Toivonen et al (2015a) demonstrated for the first time that transparent films can be achieved even in the case where aerogel technology had been used in the initial film formation; subsequent compaction yielded transparent, flexible films. …”
mentioning
confidence: 99%
“…Tammelin et al (2013) described how the application of a waterbased nanocellulose formulation to a support surface, followed by drying in place, can be a convenient way to avoid problems of shrinkage in separately-prepared films. Toivonen et al (2015a) showed that the transparency of films could be retained effectively by using REVIEW ARTICLE bioresources.com . "Nanocellulose in packaging," BioResources 12(1), 2143-2233.…”
mentioning
confidence: 99%